Playpens for Mind Children: Continuities in the Practice of Programming. - Galloway, Patricia (Information & Culture, 2012)
The article looks at the history of computer programming, with a particular focus on discussions of programming practice within the field. Details on the experiences of students in a software engineering course (SE) taught by programmer Frederick Brooks in the 1990s are presented. Topics include agency, teamwork, creativity, communication, and Agile software development.